Effects of structural transformation on magnetic properties of AlCoFeCr high-entropy soft magnetic powder cores by adjusting Co/Fe ratio. (January 2023) - Gao, Wei; Dong, Yaqiang; Ma, Yan; Wu, Hang; Jia, Xingjie; Liu, Zhonghao; Li, Xubin; Zhao, Ronglin; Wu, Shouding; Li, Qiang; He, Aina; Li, Jiawei
Graphical abstract: Highlights: Al1.5 (Cox Fe6-x )6 Cr high-entropy alloy soft magnetic powder cores were first designed and prepared via gas atomization and insulation. The effects of Co/Fe ratio on the phase formation, microstructure evolution and soft magnetic properties of the Al1.5 (Cox Fe6-x )6 Cr high-entropy alloy soft magnetic powder cores were systematically investigated. The association of magnetic domains, grain size and particle size with H c variation of Al1.5 (Cox Fe6-x )6 Cr high-entropy alloys was analyzed. Abstract: Al1.5 (Cox Fe6-x )6 Cr high-entropy alloy (HEA) soft magnetic powder cores (SMPCs) were designed and prepared via gas atomization and insulation, and the effects of the Co/Fe ratio on their phase formation, microstructure evolution, and soft magnetic properties were systematically investigated. An increase in Co content promoted the precipitation of the B2 phase from the body-centered cubic (BCC) matrix, and the content of the B2 phase was greater than that of the BCC phase at x = 4, thus replacing the BCC phase as the matrix, which contributed to the optimization of the soft magnetic properties of the AlCoFeCr HEA. The SMPC composed of the BCC single phase exhibits the lowest eddy current loss ( P e ) of 55.1 mW/cm 3 (@100 kHz, 50 mT), excellent direct current (DC) bias performance of 80.6 % at 100 Oe, and high stable effective permeability ( μ e ) of 49.9 up to 1 MHz. The association of magnetic domains, grain size, and particle size with H c variation was analyzed, providing guidelines for subsequent studies to obtain HEAs with good soft magnetic properties. By comprehensively and systematically comparing the microstructural differences of diverse matrix-phase HEAs and SMPCs, the specific application of this HEA system under high-temperature conditions can be expanded.